Impact of Prenatal Nicotine Exposure on Placental Function and Respiratory Neural Network Development - Eugenin-Leon, J; Bravo-Flores, K (Springer, 2023)
Smoking during pregnancy is associated with multiple undesirable outcomes in infants, such as low birth weight, increased neonatal morbidity and mortality, and catastrophic conditions like sudden infant death syndrome (SIDS). Nicotine, the most addictive and teratogenic substance in tobacco smoke, reaches and crosses the placenta and can be accumulated in the amniotic fluid and distributed by fetal circulation, altering the cholinergic transmission by acting on the nicotinic acetylcholine receptors (nAChRs) expressed from very early gestational stages in the placenta and fetal tissue. Because nAChRs influence the establishment of feto-maternal circulation and the emergence of neuronal networks, prenatal nicotine exposure can lead to multiple alterations in newborns. In this mini-review, we discuss the undeniable effects of nicotine in the placenta and the respiratory neural network as examples of how prenatal nicotine and smoking exposition can affect brain development because dysfunction in this network is involved in SIDS etiology. © 2023, Springer Nature Switzerland AG.